167 Methylphenidate for depression in palliative care – what's new?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Star, Angela; Candy, Bridget; Jones, Louise; Tookman, Adrian; King, Michael; Stone, Paddy
Abstract : Background: Symptoms of depression (SDEP) are common; antidepressants are not always effective or appropriate, especially in palliative care (PC) cohorts (where the priority is timely effect). Methylphenidate, a psychostimulant, may offer an alternative. The related 2008 Cochrane review 1 contained a heterogeneous group of trials and was inconclusive. New trial data has become available. Aim: To evaluate via systematic review the effectiveness and safety of methylphenidate (single-agent or adjunct) in treating depression and SDEP in adults who have advanced medical conditions or are receiving PC. Methods: We searched published papers of randomised controlled trials (RCTs) in any language from 2006-present on key online databases, manufacturer's trial listings, reference searching, and personal communication. Citations were screened in duplicate. Trials meeting criteria were collated with relevant RCTs from the previous review. 1 Cohorts with traumatic brain injury were excluded. The primary outcome measures were: effect of MPD on overall SDEP (at days 7 and 28), and adverse events (AEs). Where homogeneity allowed, meta-analysis was planned. Data were extracted and checked by two authors. Cochrane Collaboration guidelines assessed bias risk in 6-domains. GRADE criteria rated overall evidence. Results: Six papers were identified (including two from previous review), outlining five RCTs and two n-of-1 trials. Five used MPD alone and two MPD as adjunct to mirtazapine or SSRI, for a total of 229 patients. Trials compared MPD to placebo or desipramine. Small sample sizes and poor recruitment meant all trials were at high bias risk. Unfortunately, trials were heterogeneous and meaningful meta-analysis could not be performed. Most trials showed a trend toward effectiveness, however results were frequently not statistically significant. One recent trial found no evidence of effect. Methylphenidate was generally well-tolerated. Conclusion: There remains no conclusive evidence as to whether methylphenidate is an effective antidepressant in PC cohorts. Reference: . Candy, et al . Psychostimulants for depression. Cochrane Database 2008;(2):CD006722.